Identification of two‐phase recovery for interpretation of coral reef monitoring data. Issue 1 (27th October 2021) - Warne, David J.; Crossman, Kerryn A.; Jin, Wang; Mengersen, Kerrie; Osborne, Kate; Simpson, Matthew J.; Thompson, Angus A.; Wu, Paul; Ortiz, Juan‐C.
Abstract: The world's coral reefs are under threat as climate change causes increases in frequency and severity of acute thermal stress. This is compounded by chronic pressures including rises in sea surface temperature, overfishing and decline in water quality. Monitoring to understand the recovery dynamics of corals is paramount to enable effective management of coral reefs. While detailed mechanistic models provide insight into reef recovery patterns, colony scale monitoring is not viable for reefs over a large geographical extent, such as the Great Barrier Reef (GBR). Consequently, aggregated coral cover data are utilised in practice and phenomenological analysis directly applicable to these monitoring programmes is essential for reef health reporting. These analyses are especially challenging for assessment of recovery potential of reefs reduced to very low coral cover (<10%) after disturbance since standard modelling assumptions may not hold. Through the application of an innovative diagnostic approach modified from methods used in cancer cell biology, we found that almost 50% of reefs recovering from low cover exhibited a previously undocumented initial phase of slower growth per unit cover before sigmoid coral cover recovery trajectories were observed. Without properly accounting for these reduced growth periods, the expected performance of reefs may be overestimated immediately after disturbance events. The presence of two‐phase recovery patterns has a profound negative impact on the continued provision of ecological services from these reefs as major disturbance frequencies increase. Projections show that if the time between major disturbances is <5 years, then reefs with two‐phase growth are never likely to reach 15% cover. Synthesis and applications . This work provides a method to detect two‐phase recovery, the tendency for observed reef recovery to be slower than expected after a major disturbance. This phenomenon is observed across the Great Barrier Reef with serious implications for recovery potential as major disturbances occur more frequently due to climate change. Identification of reefs prone to two‐phase recovery can assist the triage of reefs for intervention actions in response to disturbances. Understanding mechanisms will inform interventions and management actions targeted towards the unique marine ecosystems across the world's reefs. Abstract : This work provides a method to detect two‐phase recovery, the tendency for observed reef recovery to be slower than expected after a major disturbance. This phenomenon is observed across the Great Barrier Reef with serious implications for recovery potential as major disturbances occur more frequently due to climate change. Identification of reefs prone to two‐phase recovery can assist the triage of reefs for intervention actions in response to disturbances. Understanding mechanisms will inform interventions and management actions targeted towards the unique marine ecosystems across the world's reefs.